Hydrogen (H2) is on the rise – is Germany on the right track? - Novak, David (Archives of Business Research, 2020)
Purpose: The anthropogenic greenhouse gas emissions cause the global temperature rise. The solution must therefore be combinations that together do not produce any greenhouse gases. Green produced hydrogen (H2) is a profound example of this, but is still at the very beginning of a comprehensive development and solution for numerous applications. As a large technology nation, Germany has a special focus and responsibility. Design / methodology / approach: Due to the fact that practically all information on this is only press releases from the media, only public media can be used, especially for the latest findings. This also includes statements from the federal and state governments and other public authorities done in personnel interviews to the author by phone. Results: Since H2 is a completely new field in the course of decarbonization and will result in investments of billions in every country, the answer to the research question posed for Germany at least can be: Yes, Germany is definitely on the right track with H2. Research / practical implications: Future research should deal with the implementation of the H2 application and the challenge of supply and demand. Originality / Value: This paper is based on brand new publications and 2 interviews with key decision makers about investments in new hydrogen plants.